Nitrate: A Crucial Signal during Lateral Roots Development - Sun, Cui-Hui; Yu, Jian-Qiang; Hu, Da-Gang (Frontiers in Plant Science, 2017)
Root plasticity is an important trait for plants to forage nutrient and adapt to survival in a complicated environment. Lateral roots (LRs) are generally more sensitive than primary roots (PRs) in response to changing environmental conditions. As the main source of nitrogen for most higher plants, nitrate acting as a signal has received great attention in the regulation of LR development. In general, there are dual effects including stimulatory and inhibitory of low nitrate on LR development; while high nitrate supply has an inhibitory effect on LR development; nitrate heterogeneity also has a stimulatory effect on LR development in NO3– rich zone. Here, we focus on recent progresses in the role of a nitrate signal in the regulation of the LRs development.